2019
DOI: 10.1007/s00261-019-02269-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of radiomics in differential diagnosis of chromophobe renal cell carcinoma and renal oncocytoma

Abstract: Purpose To explore the value of CT-enhanced quantitative features combined with machine learning for differential diagnosis of renal chromophobe cell carcinoma (chRCC) and renal oncocytoma (RO). Methods Sixty-one cases of renal tumors (chRCC = 44; RO = 17) that were pathologically confirmed at our hospital between 2008 and 2018 were retrospectively analyzed. All patients had undergone preoperative enhanced CT scans including the corticomedullary (CMP), nephrographic (NP), and excretory phases (EP) of contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…This hypothesis was also proven by the results of this study, in which the radiomics signature outperformed the image features model in predicting tumor necrosis in ccRCC. Consistent with previous studies, the radiomics signature consists mainly of three-dimensional texture features, and its prediction performance was significantly better than that of morphological features and first-order features (26,27). The reason is that the three-dimensional texture features can provide gross characterization of tumor heterogeneity through analysis of the distribution and relationship with gray levels of pixels or voxels in CT images (28).…”
Section: Discussionsupporting
confidence: 81%
“…This hypothesis was also proven by the results of this study, in which the radiomics signature outperformed the image features model in predicting tumor necrosis in ccRCC. Consistent with previous studies, the radiomics signature consists mainly of three-dimensional texture features, and its prediction performance was significantly better than that of morphological features and first-order features (26,27). The reason is that the three-dimensional texture features can provide gross characterization of tumor heterogeneity through analysis of the distribution and relationship with gray levels of pixels or voxels in CT images (28).…”
Section: Discussionsupporting
confidence: 81%
“…Li et al explored the clinical value of radiomics-based approaches, by combining TA with five ML-based models, to differentiate oncocytoma from chRCC. They found that all five classifiers performed well at differentiating between the two with AUC values over 0.85 and concluded that their approach provides valuable preoperative diagnostic accuracy [29]. Other studies used DL approaches such as convolutional neural networks (CNN) to accurately classify chRCC and oncocytoma while also achieving 100% sensitivity in comparison with final pathology results [30].…”
Section: Oncocytoma Vs Rcc Subtypesmentioning
confidence: 99%
“…In a retrospective study of 165 consecutive patients with locally advanced rectal cancer (LARC), an LR-based MR radiomics model was developed to predict the pathological complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT) in order to identify candidates for optimal treatments [25]. In a study of 61 patients with renal tumors, CT radiomics models with five ML classifiers were implemented for differential diagnosis of malignant renal chromophobe cell carcinoma (chRCC) and benign renal oncocytoma (RO) from CT images [26]. MR radiomics models with SVM and LRT were developed to differentiate benign rectal adenoma and adenoma with canceration [27].…”
Section: Rectummentioning
confidence: 99%